Pengaruh Kualitas Produk, Citra Merk, dan Iklan Terhadap Keputusan Pembelian Konsumen pada Kosmetik Purbasari Di Kota Yogyakarta - Imam Basri, Anindita; Sumarni, Murti; Lady Nor Astuti, Erika; Dyah Herdiany, Hapsari (Efektor, 2023)
The research aims to investigate whether product quality, brand image, and advertising have an impact on the purchase decision of Purbasari cosmetic consumers in Yogyakarta. The population refers to Purbasari cosmetic consumers in Yogyakarta. The research sample consists of 100 respondents, selected through purposive sampling. Data is collected through primary data from a questionnaire distributed to the respondents. The analysis used is multiple linear regression analysis. The calculation process is done using IBM SPSS 20. The results of the research indicate that product quality, brand image, and advertising have a significant impact on purchase decision simultaneously.